Konsistensi Al-Wāḥidī (w. 465/1076) dalam Menggunakan Asbāb Al-Nuzūl : Analisis Kitab Al-Wasīṭ fī Tafsīr Al-Qur’ān Al-Majīd - Mundzir, Muhammad; Farhani, Karina Rahmi Siti (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2023)
The verses found in the Qur'an are not detached from their historical context, known as asbāb al-nuzūl, playing an essential role in the practice of interpreting the Qur'an. Known as a medieval commentator and the author of the book entitled Asbāb al-Nuzūl al-Qur’ān, al-Wāḥidī emerged as one of the critical scholars in examining and citing from the reasons for revelation of verses. This article attempts to elucidate the consistency of Al-Wāḥidī in the process of interpreting the Qur'an by focusing on one of his exegesis works, Al-Wasīṭ Fī Tafsīr Al-Qur’ān Al-Majīd. By employing the main principle of asbāb al-nuzūl as a tool for interpretation and historical tracing of the descent of Qur'anic verses, the author finds that in terms of the concept of asbāb al-nuzūl formulated by al-Wāḥidī, there is not much deviation from the main principle of asbāb al-nuzūl. However, regarding the use of asbāb al-nuzūl as an element in interpretation, al-Wāḥidī tends to be inconsistent in interpretations based on Asbāb al-Nuzūl al-Qur’an in his exegesis book, Al-Wasīṭ Fī Tafsīr Al-Qur’ān Al-Majīd.